2020
DOI: 10.3390/rs12203412
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Reduced Air and Road Traffic Decreased Artificial Night-Time Skyglow during COVID-19 Lockdown in Berlin, Germany

Abstract: Artificial skyglow, the brightening of the night sky by artificial light at night that is scattered back to Earth within the atmosphere, is detrimental to astronomical observations and has an impact on ecosystems as a form of light pollution. In this work, we investigated the impact of the lockdown caused by the COVID-19 pandemic on the urban skyglow of Berlin, Germany. We compared night sky brightness and correlated color temperature (CCT) measurements obtained with all-sky cameras during the COVID-19 lockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 40 publications
3
23
0
1
Order By: Relevance
“…We also expect to use multispectral sensors covering the blue to the NIR range to study urban lighting more effectively in the future. Artificial night time skyglow as a supplement to night time light remote sensing data is affected by air quality [62,63]. Air pollution decreases due to COVID-19 city lockdown [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…We also expect to use multispectral sensors covering the blue to the NIR range to study urban lighting more effectively in the future. Artificial night time skyglow as a supplement to night time light remote sensing data is affected by air quality [62,63]. Air pollution decreases due to COVID-19 city lockdown [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Derryberry et al ( 2020 ) observed that reduced noise pollution due to the lockdown immediately yielded benefits to wildlife (specifically birds). Reduced artificial light during the lockdowns (Jechow and Hölker 2020 ) may show similar benefits.…”
Section: Rare and Unique Opportunities For Researchmentioning
confidence: 99%
“…In the global fighting against the COVID-19 epidemic, NTL data has been used to assess its broad and profound impacts ( Small and Sousa, 2021 ). Generally, the decline in night lights after lockdown was observed worldwide ( Jechow and Hölker, 2020 ). Elvidge et al (2020) found that 82% of the population lived in administrative units where lighting dimmed because of the lockdown of cities in China.…”
Section: Introductionmentioning
confidence: 99%